ZigBee’s Received Signal Strength and Latency Evaluation under Varying Environments - Sherazi, H. H. R.; Iqbal, Razi; Ul Hassan, Sana; Chaudary, M. H.; Gilani, Syed Asfandyar (Journal of Computer Networks and Communications, 2016)
Being self-configured, self-organized, and self-healing low power technology, ZigBee has obtained significant attention in last few years for achieving ubiquitous communication among various devices within a Personal Area Network (PAN). Even after a decade of its emergence, it has been well serving the communication needs of numerous modern applications belonging to multiple industries and is still a spotlight for the researchers working on certain aspects to enhance productivity along with a major cost reduction. Despite its robust communication nature, it heavily depends upon the context and is prone to the external effects that may cause a serious threat to prospective applications. This paper presents the novel experimental analysis conducted on real test beds to evaluate the impact of continuously changing communication environment on various parameters, for example, RSSI (Received Signal Strength Indicator) and latency in the presence of multiple obstacles that may lead to severe degradation in the overall performance. Eventually, we suggest a suitable frame size for ZigBee based on our results deduced from the experimental study.